Sosialisasi Pentingnya Literasi Membaca Bagi Siswa SD di Kampung Sungai Salak Pesisir Selatan - Eni Desfitri; Risa Yulisna; Fadhillah (INTEGRATIF: Jurnal Pengabdian Kepada Masyarakat, 2023)
Literacy cannot be separated from language. A person is said to have literacy skills if he has acquired basic language skills, namely reading and writing. In the world of education, reading and writing are absolutely necessary. As educators, we must continue to strive to encourage and guide students to cultivate literacy activities. Reading and writing are the basic knowledge to move on to other sciences. If you can read and write, other sciences can be learned easily. Besides being able to read and write, literacy also includes understanding the meaning of a text. The results of the activity "Socialization of the Importance of Reading Literacy for Elementary School Students in Kampung Sungai Salak Pesisir Selatan" is that it can make it easier for students to understand the material and be able to apply it in everyday life.